1984
DOI: 10.1002/j.1460-2075.1984.tb02124.x
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in several tissues share antigenic determinants with liver gap junctions.

Abstract: Using affinity-purified antibodies against mouse liver gap junction protein (26 K), discrete fluorescent spots were seen by indirect immunofluorescence labelling on apposed membranes of contiguous cells in several mouse and rat tissues: pancreas (exocrine part), kidney, small intestine (epithelium and circular smooth muscle), Fallopian tube, endometrium, and myometrium of delivering rats. No reaction was seen on sections of myocardium, ovaries and lens. Specific labeling of gap junction plaques was demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 26 publications
8
67
0
Order By: Relevance
“…In mammals, such a dominant negative effect of point mutations of connexin genes will be more pronounced with connexin genes other than the Cx32 gene; since the Cx32 gene is on the X-chromosome, no such effect will be seen in males and one of the two alleles is silent anyway in females (Migeon, 1994). In most cell types, several species of connexin genes are expressed (Dermietzel et al, 1984;Dermietzel and Spray, 1993;Nicholson et al, 1987). It has recently been reported that two different types of connexins can form chimeric connexons in insects (Stauffer, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, such a dominant negative effect of point mutations of connexin genes will be more pronounced with connexin genes other than the Cx32 gene; since the Cx32 gene is on the X-chromosome, no such effect will be seen in males and one of the two alleles is silent anyway in females (Migeon, 1994). In most cell types, several species of connexin genes are expressed (Dermietzel et al, 1984;Dermietzel and Spray, 1993;Nicholson et al, 1987). It has recently been reported that two different types of connexins can form chimeric connexons in insects (Stauffer, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The connexins belong to a multigene family, containing at least 12 members, whose cDNAs have been isolated from mammalian genomes (Kumar and Gilula, 1992). The expression pattern of each Cx species is different among tissues and changes during differentiation or development (Dermietzel et al, 1984;Dermietzel and Spray, 1993;Nicholson et al, 1987). Depending on the precise combination of connexins, connexons composed of one type may be able to form functional gap junctions with another connexon composed of other types (heterotypic) (Elfgang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Labeling of Cx4O and Cx43 proteins for immunofluorescence was performed on cultured HeLa cells grown on round glass coverslips as described previously (Dermietzel et al, 1984 Bukauskas and Weingart, 1994). In the other case, the two pipettes were connected to the cells of a cell pair spontaneously formed in culture (preformed cell pairs).…”
Section: Immunofluorescence Analysismentioning
confidence: 99%
“…After fixation, the tissue blocks were washed in PBS (three times for 15 min), then treated with 0.5 mg/ml sodium borohydride, and freshly dissolved in PBS (three times for 15 rain) to reduce free aldehyde groups. Small pieces of the fixed tissue were either immersed in 2.3 M sucrose in PBS and then processed for ultracryotomy on an ultracryotome (model FC-4D, Reichert Jung, Vienna, Austria) (18) or the tissue samples were embedded in LR-White (London Resin Co., Woking, United Kingdom) at 4°C as described in detail previously (22). Polymerization was performed in closed gelatine capsules at 4°C with UV light (360 nm).…”
Section: Immunoelectron Microscopymentioning
confidence: 99%
“…Ultrathin sections of the resin-embedded tissue were collected on water and retrieved to gold grids. Antibody labeling of the grids and processing for EM was done at room temperature exactly as described in previous papers (18,22,68). All affinity-purified primary antibodies were used at an IgG concentration of 10-50 Ixg/ml.…”
Section: Immunoelectron Microscopymentioning
confidence: 99%